Evaluating enterovirus diversity among symptomatic patients in Hungary during and after easing the COVID-19 lockdown - Nóra Deézsi-Magyar; Gyula Zsidei; Norbert Kiss; Bereniké Novák; Marianna Mezősi-Csaplár; Katalin Réka Tarcsai; Adrienne Lukács; Erzsébet Barcsay; Katalin Szomor; Mária Takács (Virology Journal)
Abstract Background The COVID-19 pandemic led to widespread public health interventions that significantly affected the transmission of various pathogens, including enteroviruses (EVs). EVs exhibit considerable genetic diversity and can cause clinical manifestations ranging from mild illnesses to severe diseases. Our present study aimed to evaluate the diversity of circulating EV types in Hungary and assess the impact of lockdown measures on EV prevalence based on testing clinical samples obtained from symptomatic patients. Methods As part of the routine enterovirus diagnosis, we conducted quantitative reverse transcription polymerase chain reaction (RT-qPCR) on clinical samples obtained from patients presenting with symptoms corresponding to EV infection. Positive samples were then subjected to virus isolation in cell culture and next-generation sequencing (NGS). Phylogenetic analysis was performed to place the newly generated sequences within the global diversity of EV strains for comparison. Results During this period, an overall number of 125 patients tested positive for EVs, mostly children under the age of 15 years. The most common symptoms were fever, hand-foot-mouth disease, encephalitis, and meningitis. The temporal distribution of EV-positive cases showed strong seasonality, with peaks in the summer and autumn months. The lowest number of confirmed cases occurred during the lockdown years, attributed to limited sample collection and reduced personal contacts. However, following the easing of restrictions, the number of cases significantly increased, with the highest incidence observed in 2022. The distribution of EV genotypes shifted notably after easing the lockdowns. While only coxsackievirus (CV)A6 was detected during 2021, a broader range of genotypes emerged afterwards, including CVA10, CVA16, echovirus E9, and E11. Conclusions Next-generation sequencing analysis revealed notable genotypic diversity, providing valuable insights into the evolution of EVs in Hungary and across Europe. These findings underscore the importance of continued surveillance of enterovirus infections, particularly in the context of pandemic recovery, as the shifting EV genotype landscape may impact disease severity and spread, highlighting the need for adaptive public health responses.